Pengembangan Lembar Kerja Anak Berbasis Pendekatan Saintifik Bermuatan Moderasi Beragama untuk Raudhatul Athfal - Edi Bahtiar; Any Umy Mashlahah (MODELING: Jurnal Program Studi PGMI, 2025)
This study aims to develop a Child Worksheet (LKA) based on a scientific approach that contains values of religious moderation for Raudhatul Athfal (RA). The urgency of this study stems from the need to strengthen character education from an early age in a multicultural society, as well as the limited availability of early childhood education teaching materials that are able to integrate cognitive, affective, and social aspects in a balanced manner. The research used the Education Design Research (EDR) method with stages of analysis and exploration, design and construction, as well as evaluation and reflection. The research subjects involved teachers and RA children in Jekulo District, Kudus Regency. Data collection techniques included literature studies, interviews, observations, and documentation. The results showed that the developed LKA met the criteria of didactic, constructive, and technical feasibility; was attractive to children; and was effective in supporting the understanding of learning concepts and the internalization of religious moderation values. The systematic integration of the scientific approach with indicators of religious moderation proved to help teachers create active, meaningful, and character-building learning. The novelty of this study lies in the development of an integrative-operational Islamic Early Childhood Education (PAUD) Child Worksheet (LKA) design model, which directly links the stages of the scientific approach (observing, questioning, trying, reasoning, and communicating) with indicators of religious moderation that have been simplified in accordance with the developmental characteristics of early childhood. Unlike previous studies that tended to place character values or religious moderation as normative or thematic content, this study offers an activity-based implementative framework that can be directly used by RA teachers in their daily teaching practices. Thus, the novelty of this research lies not only in the content of values, but also in the pedagogical mechanisms and instructional design of LKA that have been empirically tested in RA units. This research contributes to the development of character-based early childhood education teaching materials and provides practical implications for RA educators.